2015
DOI: 10.1128/aem.03723-14
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Conjugative Elements Are Widespread in Field Isolates of Mycoplasma Species Pathogenic for Ruminants

Abstract: Comparative genomics have revealed massive horizontal gene transfer (HGT) between Mycoplasma species sharing common ruminant hosts. Further results pointed toward an integrative conjugative element (ICE) as an important contributor of HGT in the small-ruminant-pathogen Mycoplasma agalactiae. To estimate the prevalence of ICEs in ruminant mycoplasmas, we surveyed their occurrence in a collection of 166 field strains representing 4 (sub)species that are recognized as major pathogens. Based on available sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…The minimal ICEA chassis was consistent with the conservation of cds5, cds17, cds19 and cds22 across documented ICEs of ruminant mycoplasma species (8), and the occurrence of cds1, cds14 and cds16 at very similar location in a majority of MICEs (2, 46, 23). Interestingly, the conjugative properties of M. agalactiae were also abrogated by mTn insertion in NCRs raising questions regarding the presence of regulatory elements and/or key motifs, such as an oriT , in these regions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The minimal ICEA chassis was consistent with the conservation of cds5, cds17, cds19 and cds22 across documented ICEs of ruminant mycoplasma species (8), and the occurrence of cds1, cds14 and cds16 at very similar location in a majority of MICEs (2, 46, 23). Interestingly, the conjugative properties of M. agalactiae were also abrogated by mTn insertion in NCRs raising questions regarding the presence of regulatory elements and/or key motifs, such as an oriT , in these regions.…”
Section: Discussionsupporting
confidence: 75%
“…Since their discovery in mycoplasma species of the Hominis phylogenetic group, MICEs have been found broadly distributed across Mollicutes (26, 8) and their pivotal role in HGTs is emerging (7, 12, 13). Taking advantage of the M. agalactiae ICE prototype, this study provides the first functional analysis of MICE factors involved in conjugative transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bovis is well-equipped to generate diversity. Indeed sequenced genomes have revealed insertion sequences, integrative and conjugative elements (ICEs) and vsp loci (Li et al, 2011;Qi et al, 2012;Wise et al, 2011) and field strains have recently been shown to often harbor functional ICEs (Tardy et al, 2014). As a logical consequence, the genetic heterogeneity of M. bovis isolates collected at different times has seemed to be the rule in many countries, and was reported in Europe (Kusiluka et al, 2000;McAuliffe et al, 2004;Sulyok et al, 2014), North America (BellRogers et al, 2012;Soehnlen et al, 2011) and Israel (Amram et al, 2013) etc.…”
Section: Discussionmentioning
confidence: 97%
“…The lipoproteins encoded in the D3 (MMCAP2_0014-0016; 4,677-bp region; D3) as well as the D5 region ( lppQ , MMCAP2_0889-0904; 24,906-bp region, D5) were also excised employing again the yeast-based engineering method. Finally, we deleted a large genomic region that contained the Mycoplasma -specific F1-likeX0 ATPase (15), the MIB-MIP system (9) that has been shown in vitro to modulate the action of immunoglobulins through specific degradation, an integrative and conjugative element (ICE) (16) and several genes encoding other lipoproteins. The ICE was targeted in an effort to reduce mobile elements from the Mmc genome.…”
Section: Resultsmentioning
confidence: 99%